Complete mitochondrial genome of tragulus kancil and tragulus napu in peninsular Malaysia - Suleiman, Asia Abdillahi (2023)
The tropical country of Malaysia has a unique ecosystem, located in the southeast Asian region and sharing a border with Thailand,Singapore,Burnei and Indonesia. Malaysian conservation authorities have identified the need to conserve their natural resources and environment including floral and faunal. These include Tragulidae which is a small family group with 3 genera and 2 species. Two of Tragulidae species are T.kancil and T.napu that native to Peninsular Malaysia are facing a crucial threat of extinction including habitat degradation, forest fragmentation, illegal hunting, and trading. These threats are leading to decline in their population size. The present study involved full mitochondrial DNA (mtDNA) genomic sequence using next generation sequencer platform of T.kancil and T.napu from Peninsular Malaysia for the first time. A total of 17 individuals of Tragulus spp. were used to collect tissue specimens. There were 10 T.kancil individuals and triplet samples of a T.napu which were collected from Perlis and Perak. Additional six of those 17 were T.kancil samples sent to wildlife forensic laboratory from Selangor, Phang,Kedah,Perak and Sarawak as a part of routine operations. In phylogenetic tree, T.kancil are different from their lesser Tragulus relative (T.javanicus). Unlike T.napu where a clear distiniction can be observed between a T.napu samples from Malaysia (Perlis) versus a T.napu from Thailand, no full mtDNA reference sequence of T.kancil from other country is currently available for geographical comparison. Overall, the whole mtDNA genomic data collected from T.kancil and T.napu support the current classification of Tragulus and distinication between Tragulus and Rusa species.